Consequences of Low Risk and Hazardous Alcohol Consumption among University Students in Australia and Implications for Health Promotion Interventions - Burns, Sharyn; Crawford, Gemma; Hallett, Jonathan; Jancey, Jonine; Portsmouth, Linda; Hunt, Kristen; Longo, J. (Scientific Research Publishing, 2015)
Background: Hazardous alcohol consumption and associated harms are high among young university students. The university environment is conducive to excessive alcohol consumption with studies finding young university students to drink alcohol at higher levels than their non-university peers. Methods: A random sample of 18 - 24-year-old undergraduate, internal university students completed a survey (n = 2465) to investigate differences in self-reported personal, secondhand and witnessed alcohol-related harms, alcohol expectancies, pre-loading, and friends’ alcohol consumption between low risk and hazardous drinkers. Univariate and multivariate analyses are reported. Results: Almost 40% of students who had consumed alcohol in the past year reported drinking at hazardous levels. Univariate analyses found students who reported hazardous drinking reported significantly higher scores relating to experienced, second-hand, witnessed and academic problems compared to low risk drinkers. Hazardous drinkers were also more likely to pre-load, to drink at higher levels when pre-loading, have more friends who drank alcohol, have more friends who drank at hazardous levels and to score higher on alcohol expectancies. However both low risk and hazardous drinkers experienced a range of harms due to their own drinking including hangover (71.2%), unprotected sex (19.3%), regretted sex (16.8%) and drink-driving (17%).Looking after an intoxicated student (34.3%) and witnessing someone pass out (37.5%) were issues for all drinkers. Experienced alcohol related harms, academic problems, alcohol expectancies, close friends’ level of alcohol consumption, pre-loading in the last four weeks and level of consumption when pre-loading were predictors of hazardous drinking (p < 0.001). Conclusion: Young undergraduate university students are at risk of a range of academic, social, emotional and physical harms associated with their own and other students’ alcohol consumption. There is a need for integrated programs to address university drinking culture and effect positive changes.